2021
DOI: 10.3389/fbioe.2021.781608
|View full text |Cite
|
Sign up to set email alerts
|

RGD Peptide-Conjugated Selenium Nanocomposite Inhibits Human Glioma Growth by Triggering Mitochondrial Dysfunction and ROS-Dependent MAPKs Activation

Abstract: Chemotherapy is still one of the most common ways to treat human glioblastoma in clinic. However, severe side effects limited its clinic application. Design of cancer-targeted drugs with high efficiency and low side effect is urgently needed. Herein, silver nanoparticles (Ag NPs) and nano-selenium (Se NPs) conjugated with RGD peptides (Ag@Se@RGD NPs) to target integrin high-expressed glioma were designed. The results found that Ag@Se@RGD NPs displayed stable particle size and morphology in physiological condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The suppression of the expression of kinases involved in growth-factor-associated growth and survival of cells likely contributed to the reduction In the survival of tumor cells and the activation of apoptosis [ 23 ]. Liu et al (2021) [ 133 ] observed similar changes in the phosphorylation of p38, JNK, and Erk1/2 in U251 cells (human glioma). After the application of GSH (an antioxidant), they recorded a decrease in the activation of these kinases, and therefore, the authors point to the involvement of ROS in the activation of MAPK signaling pathways.…”
Section: The Potential Of Agnps In Nano-oncologymentioning
confidence: 83%
“…The suppression of the expression of kinases involved in growth-factor-associated growth and survival of cells likely contributed to the reduction In the survival of tumor cells and the activation of apoptosis [ 23 ]. Liu et al (2021) [ 133 ] observed similar changes in the phosphorylation of p38, JNK, and Erk1/2 in U251 cells (human glioma). After the application of GSH (an antioxidant), they recorded a decrease in the activation of these kinases, and therefore, the authors point to the involvement of ROS in the activation of MAPK signaling pathways.…”
Section: The Potential Of Agnps In Nano-oncologymentioning
confidence: 83%
“…Our previous work also indicated that Se NPs could induce cancer cell apoptosis by inhibiting EGFR-mediated PI3K/AKT and Ras/Raf/MEK/ERK pathways after loading with oridonin ( 53 ). What is more, it is reported that Se NPs could trigger MAPK activation and the caspase-3 signal pathway, eventually inducing apoptosis of tumor cells ( 54 , 55 ). These results suggest that Se NPs could serve as strong apoptosis-induction agents, which therefore shows the potential of Se NPs as novel antitumor agents by inducing cancer cell apoptosis.…”
Section: Se Nps Induce Apoptosismentioning
confidence: 99%
“…Similarly, Song et al synthesized "smart" nanosystems based on Se NPs modified with HER-2 antibody for effective delivery into the brain tumor [299]. Wenjian has developed inorganic hybrids made of Ag and Se NPs (Ag@Se NPs) for the GBM therapy [300]. Ag@Se NPs were conjugated with RGD peptides (Ag@Se-RGD NPs) for GBM targeting.…”
Section: Se Npsmentioning
confidence: 99%
“…Ag@Se NPs were conjugated with RGD peptides (Ag@Se-RGD NPs) for GBM targeting. The results showed that Ag@Se-RGD NPs possessed high in vitro stability and induced a significant intracellular uptake by human glioma cells U251 with the following cell apoptosis due to ROS effect [300].…”
Section: Se Npsmentioning
confidence: 99%